Literature Review: Impact of Organophosphate Pesticide Exposure on Cholinesterase Enzyme Activity and Associated Risk Factors for Poisoning, 2017-2020 - Rania Ichwana Wicaksono; Eka Saul Manuel; Aditya Sukma Pawitra; Khuliyah Candraning Diyanah; Soedjajadi Keman; R. Azizah; Ririh Yudhastuti (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Organophosphate pesticides, which are used to control pests of crops, affect the nervous system by inhibiting the activity of cholinesterase enzymes in the body. This can be achieved by inhaling, eating, or applying it to the skin. This study research aims to determine the level of pesticide exposure that can inhibit the activity of the Cholinesterase enzyme in the blood. This study employed a systematic literature review with library sources used through Google Scholar and Science Direct, resulting in 16 research articles discussing cholinesterase enzyme activity due to exposure to organophosphates discussed in 2017-2020. Discussion: The results of a previous study found that exposure to organophosphates significantly reduced cholinesterase enzyme activity by 50-80%. Testing for cholinesterase as a biomarker of exposure to Organophospate (OP) through acetylcholinesterase activity in red blood cells (AChE). This study explored the relationship between gender, age, knowledge of farmers, personal protective equipment, farmers' smoking behavior, and duration of spraying. Conclusion: Poisoning alters the activity of cholinesterase enzymes in the blood of farmers, resulting in acute and chronic health problems. Several factors have been found to correlate with organophosphate poisoning, including age, level of knowledge among farmers, use of personal protective equipment, smoking behavior, and duration of spraying activities.